Learning Apache Maven : Java build and management and automation - Bowersox, Kevin; Safari eBooks ([Place of publication not identified] : Infinite Skills, 2015)
"In this Learning Apache Maven training course, expert author Kevin Bowersox will teach you how to perform Java builds more efficiently with Maven. This course is designed for intermediate Java developers."--Resource description page.
Title from resource description page (viewed May 11, 2015)
Presenter, Kevin Bowersox.
Keywords: Apache (Computer file : Apache Group); Application software -- Development; Project management -- Software; Java (Computer program language); Electronic books